Student participation in clinical handover–an integrative review. Issue 5 (18th January 2016) - Malone, Linda; Anderson, Judith; Manning, Jennifer
Abstract : Aim and objectives: To examine the literature exploring the current understanding of student nurse participation in clinical handover whilst they are enrolled in an undergraduate preregistration course. Background: The importance of handing over the care of a patient to ensure continuity and safety of care is well‐recognised. Effective preparation of student nurses to competently perform this critical task requires the use of appropriate teaching strategies to support this learning, within undergraduate preregistration nursing programs. Design: An integrative literature review. Method: An integrative literature review was conducted to establish what is known about student nurse participation in relation to clinical handover. This resulted in 18 articles for inclusion in the literature review. An analysis was then undertaken of these 18 articles to extract key themes. Results: Learning and teaching strategies need to address a variety of methods of the clinical handover process including verbal and written handovers. Participating in clinical handover prior to being given the responsibility of patient care prepares students for the workplace. Key themes identified within the literature included: learning strategies, limitations and challenges involved in putting theory into practice, handover structure and issues regarding confidentiality. Conclusion: Simulation and clinical practice are commonly used to prepare students for this role during their undergraduate education. The use of simulation and structured handover techniques prior to clinical placement increases student confidence to engage in clinical handovers during their clinical placements. Relevance to clinical practice: This article raises the awareness of both clinical staff and educators as to the need for student nurses to develop their skills in clinical handover practice and suggests strategies to prepare student nurses to conduct clinical handover competently in the clinical setting.